2008
DOI: 10.1002/bies.20756
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing new dimensions in Drosophila myoblast fusion

Abstract: SummaryOver several years, genetic studies in the model system, Drosophila melanogastor, have uncovered genes that when mutated, lead to a block in myoblast fusion. Analyses of these gene products have suggested that Arp2/3-mediated regulation of the actin cytoskeleton is crucial to myoblast fusion in the fly. Recent advances in imaging in Drosophila embryos, both in fixed and live preparations, have led to a new appreciation of both the three-dimensional organization of the somatic mesoderm and the cell biolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 58 publications
(124 reference statements)
3
18
0
Order By: Relevance
“…However, the ability of Hbs to drive fusion beyond precursor formation when in excess, and the observation that removal of one copy of sns enhances fusion defects in hbs mutants, suggests that Hbs can assist in later rounds of myoblast fusion. These data are consistent with models in which molecular interactions in precursor formation and subsequent fusion differ kinetically but not genetically Richardson et al, 2008). One possibility, independent of the process of fusion itself, is that Sns and Hbs differ in their ability to drive FCM cell migration.…”
Section: Hbs Does Not Replace Sns: Implications For Signal Transductisupporting
confidence: 87%
See 2 more Smart Citations
“…However, the ability of Hbs to drive fusion beyond precursor formation when in excess, and the observation that removal of one copy of sns enhances fusion defects in hbs mutants, suggests that Hbs can assist in later rounds of myoblast fusion. These data are consistent with models in which molecular interactions in precursor formation and subsequent fusion differ kinetically but not genetically Richardson et al, 2008). One possibility, independent of the process of fusion itself, is that Sns and Hbs differ in their ability to drive FCM cell migration.…”
Section: Hbs Does Not Replace Sns: Implications For Signal Transductisupporting
confidence: 87%
“…An alternative model, using three dimensional analyses and quantitating fusing myoblasts over time, revealed that fusion occurs in two temporal phases, comprising an initial phase of limited fusion between cells that are in close proximity and a second phase when most myoblast fusion occurs . Moreover, precursor formation is temporally delayed in embryos lacking molecules such as Rols and Kette, suggesting that these molecules do influence the first step in fusion Richardson et al, 2008). The present study does not address whether the genetic requirements for precursor formation differ from those for subsequent rounds of fusion, or whether these steps utilize the same set of proteins.…”
Section: Hbs Does Not Replace Sns: Implications For Signal Transductimentioning
confidence: 79%
See 1 more Smart Citation
“…Furthermore, we describe transient F-actin structures that form in myoblasts near the onset of fusion, under the influence of the Arp2/3 actin polymerization machinery, but independently of the Wsp and SCAR nucleating systems. These findings underscore the significant roles played by the actin-based cytoskeleton in the myoblast fusion process (Onel and Renkawitz-Pohl, 2009;Richardson et al, 2008), and, in particular, generalize and accentuate the myogenic role of the WASp pathway.…”
Section: Introductionmentioning
confidence: 54%
“…These studies indicate that these fusion genes are required for the dissolution of this structure during the fusion process and suggest that removal of this actin structure is crucial for fusion to proceed (Richardson et al, 2008a;Richardson et al, 2007). In addition, several studies proposed that this actin structure at the fusion site is required for vesicle trafficking (Kim et al, 2007) and/or enlarging fusion pores (Berger et al, 2008;Massarwa et al, 2007).…”
Section: Introductionmentioning
confidence: 95%